Analyzing Banking Risk : A Framework for Assessing Corporate Governance and Risk Management, Third Edition - Van Greuning, Hennie (World Bank, 2012)
This publication aims to complement existing methodologies by establishing a comprehensive framework for the assessment of banks, not only by using financial data, but also by considering corporate governance. It argues that each of the key players in the corporate governance process (such as shareholders, directors, executive managers, and internal and external auditors) is responsible for some component of financial and operational risk management. Following a holistic overview of bank analysis in chapter two, the importance of banking supervision in the context of corporate governance is discussed in chapter three. This chapter also considers the partnership approach and the emerging framework for corporate governance and risk management, as well as the identification and allocation of tasks as part of the risk management process. The framework for risk management is further discussed in chapters four through eleven.